EXPERIMENTAL SUBSTANTIATION EFFICIENCY OF APPLICATION OF THE AMARANTH SEEDS OIL AT COMPLICATIONS INVOKED BY ISONIAZID - Ekaterina Muzalevskaya (Belgorod National Research University, 2016)
In an experimental research found that amaranth seeds press oil in dose of 600 mg/kg of the Isoniazid intoxication (in dose of 542 mg/kg during 6 days) prevents death of animals, reduces considerably an expressiveness of central and peripheral nervous system pathological changes, promotes normalization of digestive function and animals clinical state, lowers cytolysis syndrome manifestation degree promoting full normalization of aminotransferases activity on the 14th day. By means of biomicroscopy, using the original method of rats small intestine mesentery microvascular monitoring in an abdominal cavity, the peculiarities of microcirculatory processes disturbances invoked by high doses of Isoniazid, are revealed for the first time and the possibility of it correction via amaranth seeds oil.